ENT 530 : Blueprint : Gemilang Sdn Bhd / Muhammad Afiq Brohan ... [et al.] - Brohan, Muhammad Afiq; Arifin, Nor Hanani; Md Din, Muhammad Zahiruddin (2018)
Gemilang Sdn. Bhd. has been established in 2018 by 3 key management personnel who have background in both environmental technology and business management fields. They are Muhammad ZahirruddinBin Md Din as general manager, Muhammad Afiq Bin Brohan as administration manager and operation manager then Nor Hanani Binti Arifinas marketing manager and financial manager.